Construction of chitin functional materials based on a "green" alkali/urea solvent and their applications in biomedicine: Recent advance. (June 2021) - Bi, Shichao; Li, Fang; Qin, Di; Wang, Mengyang; Yuan, Shipeng; Cheng, Xiaojie; Chen, Xiguang
Highlights: Alkali/urea is a green and environmentally friendly dissolving system of chitin. A variety of recycled chitin materials have been prepared based on alkali/urea solution. Chitin-based functional materials show application potential in various fields. The application of chitin will promote the sustainable development of society. Abstract: Chitin, the nitrogen-containing polysaccharide in nature and reserves second only to cellulose, has demonstrated potential application value in multiple fields. However, under the background of various environmental problems caused by the excessive use of petroleum-based polymers, the utilization rate of this eco-friendly and renewable natural polymer is far from reaching a reasonable level. Therefore, researches on the green dissolution system of chitin and the preparation method of functional materials will undoubtedly lay a theoretical foundation for its large-scale promotion, which conform to the basic concept of sustainable development. This review will elaborate on the existing dissolution systems of chitin and focus on the establishment of a novel green alkali/urea dissolution system and its application in the preparation of functional materials. In this work, a series of chitin-based functional materials including fibers, microspheres, hydrogels, sponges, and films have been successfully prepared based on the green alkali/urea dissolution system. Furthermore, these materials were successfully applied in biomedicine such as wound healing, bone repair, cell scaffold, anti-microbial, hemostasis, cartilage repair and other fields including photoelectric, electrocatalysis and adsorption. We hope that this review can provide certain guidance for the preparation and application of chitin-based green polymer materials to promote the sustainable development of human society. Graphical abstract: Preparation of chitin based functional materials based on green alkali/urea dissolution system and their application in biomedicine such as wound healing, bone repair, cell scaffold, antibiosis, hemostasis, cartilage repair and other fields like electrocatalysis and adsorption. Image, graphical abstract